Sustained yet non-curative response to lenalidomide in relapsed angioimmunoblastic T-cell lymphoma with acquired chidamide resistance: a case report with 10-year follow-up, genetic insights and literature review - Xu, Juan; Huang, Jie; Xie, Liping; Liu, Ting; Li, Jianjun; Chen, Xinchuan; Liu, Zhigang; Zhao, Sha; Xu, Caigang; Wu, Yu (Frontiers in Oncology, 2024)
Angioimmunoblastic T-cell lymphoma (AITL) is an aggressive subtype of peripheral T-cell lymphoma (PTCL) characterized by its T-follicular helper (TFH) phenotype. Relapsed and refractory disease is common in AITL and often associated with a poor prognosis. The presence of epigenetic abnormalities, immune dysregulation, hyperinflammation and active angiogenesis in AITL offers potential targets for histone deacetylase (HDAC) inhibitors and immunomodulatory drugs (IMiDs). Herein, we present a case of AITL with multiple relapses over a decade. Following intensive chemotherapy and autologous stem cell transplantation (ASCT), the patient relapsed with extensive nodal and extranodal involvement, particularly pulmonary lesions, and subsequently pursued chemo-free treatments. Initially, the patient exhibited a remarkable response to single-agent chidamide, the first oral HDAC inhibitor. Soon after developing resistance to chidamide, continuous treatment with lenalidomide led to an impressive sustained complete remission lasting 64 months, followed by a diminished response for an additional 11 months. Genetic profiling of the patient revealed mutations in KMT2D and ARID1A, along with chromosomal aberrations such as del(5q). Notably, genes commonly mutated in AITL, including RHOA, TET2, DNMT3A, and IDH2, were absent in this case. A review of the literature highlights the heterogeneous genomic landscape of AITL and the diversity of treatment options available, underscoring the importance of tailored approaches to overcome resistance and improve outcomes in this distinct lymphoma subtype.